Model Pembelajaran Inkuiri Untuk PAUD - Rohayani, Farida farida (Program Studi Pendidikan Guru Raudlatul Athfal, UIN Sunan Kalijaga Yogyakarta, 2018)
One of the supports of successful learning is understanding and using the right model and in accordance with the theme of learning. In this study, further study and understanding of one of the learning models is the inquiry learning model. Many parents who do not understand how this learning model is not only applied in school, but also applied at home, because this learning is not always about education in school alone. This research is a literature study that uses documentation as a data collection method. The results show that: 1) this learning model could not only be applied in schools, but it was very important to be implemented at home, with direct intervention from parents, 2) by looking at the activities and learning steps offered by this model, it could improve learning outcomes and make learning more active and enjoyable, 3) each learning model will not only have advantages, but certainly has disadvantages. In this research some weaknesses and strengths were found in inquiry learning.